IN VITRO ANTIBACTERIAL EFFICACY OF PLECTRANTHUS AMBOINICUS MEDIATED SILVER NANOPARTICLES AGAINST URINARY TRACT PATHOGENS - S, SREELAKSHMY; S, THANGAPANDIYAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study is to synthesize green mediated silver nanoparticles (AgNPs) using Plectranthus amboinicus leaf extract and to evaluate its antibacterial activity against selected urinary tract infection (UTI) causing bacteria. Methods: Phytoconstituents present in leaf extract of P. amboinicus (Lour.) Spreng were analyzed by standard qualitative tests. The synthesized AgNPs were characterized by visual inspection, ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy. The antibacterial activity of synthesized AgNPs was examined against the UTI pathogens such as Pseudomonas aeruginosa, Enterobacter sp., Klebsiella pneumonia, and Escherichia coli. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of AgNPs were carried out by broth dilution method and standard plate count method, respectively. Results: Synthesized AgNPs exhibited a spherical shape with an average size of 17.3 nm. The antibacterial activity of AgNPs against tested bacterial pathogens showed a maximum inhibition zone of 22.00±1.00 mm against P. aeruginosa. The bacterial growth inhibition was confirmed by MIC and MBC. Conclusion: P. amboinicus leaf extract mediated AgNPs could be used as an effective antibacterial agent for the management of UTIs. Surface modifications of urinary catheters with AgNPs may prevent the risk of contamination and the associated infections.